Gothic Fiction in Twenty-First Century: A Psychoanalytic Study of Waters’ The Little Stranger - Latif, Midhat; Rabbani, Munazzah (Pakistan Languages and Humanities Review, 2025)
The present study aims to explore the shift in modern Gothic fiction from supernatural elements to realism and the way it incorporates psychological issues to induce fear in the readers. Gothic literature has been widely studied, but little attention has been given to the psychological aspect which this article explores. The current research is purely qualitative and analyzes Sarah Waters’ The Little Stranger (2009) using the psychoanalytic theory of Sigmund Freud to understand the psyche of various characters. The concept of repression and drives from Freudian psychoanalysis give useful insights about the way various characters react to trauma. The analysis revealed that various characters seem to be working on the death drive, harming others, and in some cases, succumbing to self-harm and suicide owing to their repressed fears and desires, giving rise to a psychologically disturbing narrative. Future researchers can analyze other modern Gothic fictions to explore psychological dimensions of the work, using various other theories.